Prevalence and factors of surgical site infections in surgical wards, Windhoek, Namibia - Anna N. Haifete; Petra Brysiewicz (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: Surgical site infection (SSI) is a prevalent healthcare-associated infection worldwide, defined as any incisional infection occurring within 30 days post-operation or within 1 year in the presence of an implant. Healthcare-associated infections represent a significant threat to patient health and continue to pose a major global challenge.